Education, scientific-research and consulting work in agriculture of Serbia - Cvijanović , Drago (Applied Studies in Agribusiness and Commerce, 2010)
Serbia has small number of producers2 which have encircled production system (from primaryproduction to processing), which do business successful, introduce marketing strategy and production standards, registered their products’ mark of origin, succeed to export on EU market, use internet or has its own internet domain, etc. For creation of such, competitive and modern agricultural producer, there is necessity for production specialization, any kind of cooperation and better organization. In same time, there is more space for bigger financial support of state, as expert and consultative support „created“ through strong partnership between public and private sector, i.e. tough and constructive cooperation of state and farmers sector, like as institutions of education, science, research and consultative work. In the paper was given review of number and territorial dispersion of educational institutions, current scientific-research work and consultative functions in agriculture in Serbia, than was pointed out main problems in their functioning and previous work and also proposed concrete suggestions for overcoming of existing limitations, as for modernization /reorganization of those institutions, in a way to be more useful for agricultural producers.